Coding Regions of Intrinsic Disorder Accommodate Parallel Functions. Issue 11 (November 2016) - Pancsa, Rita; Tompa, Peter
Abstract : Numerous DNA- and RNA-level functions are embedded in protein-coding regions, which constrains their structure, function, and evolution. Accumulating evidence suggests that such additional, overlapping functions occur preferentially in the coding sequences of intrinsically disordered proteins/regions (IDPs/IDRs), especially in those that are newly incorporated and thus have reduced selective pressure. It is the lack of strict structural constraints that makes disordered proteins more tolerant to mutations and thus more permissive to the appearance of overlapping functions within their coding sequences than structured domains. Therefore, IDPs/IDRs are often mosaics of segments fulfilling protein functionalities and intervening regions primarily carrying nucleotide-level functions. The ensuing complexification of gene-regulatory circuits may have contributed to the evolutionary spread of structural disorder in complex eukaryotic organisms. Trends: The degeneracy of the genetic code enables multiple meaningful codes to exist in parallel. Coding regions of eukaryotic genes abound in nucleotide-level functional elements. These elements constrain the structure, function, and evolution of the encoded proteins. Eukaryotic proteins are rich in intrinsically disordered proteins/regions (IDPs/IDRs) that mainly fulfill regulatory roles by means of short linear protein interaction motifs. Lacking structural constraints, IDPs/IDRs are more tolerant to mutations than structured domains. A range of recent observations implies that the coding regions of IDPs/IDRs are more prone to accommodating parallel codes. Recently acquired coding regions tend to encode IDPs/IDRs and often develop overlapping functions.